Electromechanical properties of human osteoarthritic and asymptomatic articular cartilage are sensitive and early detectors of degeneration. Issue 3 (March 2018) - Hadjab, I.; Sim, S.; Karhula, S.S.; Kauppinen, S.; Garon, M.; Quenneville, E.; Lavigne, P.; Lehenkari, P.P.; Saarakkala, S.; Buschmann, M.D.
Summary: Objective: To evaluate cross-correlations of ex vivo electromechanical properties with cartilage and subchondral bone plate thickness, as well as their sensitivity and specificity regarding early cartilage degeneration in human tibial plateau. Method: Six pairs of tibial plateaus were assessed ex vivo using an electromechanical probe (Arthro-BST) which measures a quantitative parameter (QP) reflecting articular cartilage compression-induced streaming potentials. Cartilage thickness was then measured with an automated thickness mapping technique using Mach-1 multiaxial mechanical tester. Subsequently, a visual assessment was performed by an experienced orthopedic surgeon using the International Cartilage Repair Society (ICRS) grading system. Each tibial plateau was finally evaluated with μCT scanner to determine the subchondral-bone plate thickness over the entire surface. Results: Cross-correlations between assessments decreased with increasing degeneration level. Moreover, electromechanical QP and subchondral-bone plate thickness increased strongly with ICRS grade ( ρ = 0.86 and ρ = 0.54 respectively), while cartilage thickness slightly increased ( ρ = 0.27). Sensitivity and specificity analysis revealed that the electromechanical QP is the most performant to distinguish between different early degeneration stages, followed by subchondral-bone plate thickness and then cartilage thickness. Lastly, effect sizes of cartilage and subchondral-bone properties were established to evaluate whether cartilage or bone showed the most noticeable changes between normal (ICRS 0) and each early degenerative stage. Thus, the effect sizes of cartilage electromechanical QP were almost twice those of the subchondral-bone plate thickness, indicating greater sensitivity of electromechanical measurements to detect early osteoarthritis. Conclusion: The potential of electromechanical properties for the diagnosis of early human cartilage degeneration was highlighted and supported by cartilage thickness and μCT assessments.